2001
DOI: 10.1161/hy1101.096109
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Pathophysiological Functions of the AT 2 Subtype Receptor of Angiotensin II

Abstract: Abstract-Angiotensin II exerts a potent role in the control of hemodynamic and renal homeostasis. Angiotensin II is also a local and biologically active mediator involved in both endothelial and smooth muscle cell function acting on 2 receptor subtypes: type 1 (AT 1 R) and type 2 (AT 2 R). Whereas the key role of AT 2 R in the development of the embryo has been extensively studied, the role of AT 2 R in the adult remains more questionable, especially in humans. In vitro studies in cultured cells and in isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 108 publications
(108 reference statements)
3
78
0
3
Order By: Relevance
“…In contrast, AT 2 is mainly present during fetal development (and is believed to have an essential role in physiological vascular development) but decreases rapidly after birth. 5,6 In adults, expression of AT 2 under normal conditions is largely restricted to the adrenals, kidneys, uterus, ovary, heart, and specialized nuclei in the brain, but it is upregulated in various pathological conditions associated with tissue remodeling or inflammation, including hypertension, heart failure, postmyocardial infarction, ischemia, and diabetes. 2,5,7 Multiple hormonal, cytokine, and metabolic factors are involved in upregulating AT 2 densities on cell surfaces.…”
Section: Location and Expression Of At 2 Relative To At 1 In Normal Amentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, AT 2 is mainly present during fetal development (and is believed to have an essential role in physiological vascular development) but decreases rapidly after birth. 5,6 In adults, expression of AT 2 under normal conditions is largely restricted to the adrenals, kidneys, uterus, ovary, heart, and specialized nuclei in the brain, but it is upregulated in various pathological conditions associated with tissue remodeling or inflammation, including hypertension, heart failure, postmyocardial infarction, ischemia, and diabetes. 2,5,7 Multiple hormonal, cytokine, and metabolic factors are involved in upregulating AT 2 densities on cell surfaces.…”
Section: Location and Expression Of At 2 Relative To At 1 In Normal Amentioning
confidence: 99%
“…The latter possibility is suggested by the finding in experimental studies that AT 2 -dependent NO production can only be observed after AT 1 blockade by losartan. 6,8 Thus, although AT 2 is present in the vasculature in adults, its distribution is not homogeneous and is subject to changes according to age, vessel type, and the presence of patholog-ical states. This raises the important question of their function in the cardiovascular system relative to that of AT 1 .…”
Section: Location and Expression Of At 2 Relative To At 1 In Normal Amentioning
confidence: 99%
See 1 more Smart Citation
“…Several molecules, including ERK1 and ERK2, have been involved in anG ii-induced VSMc proliferation (27). aT2r is abundantly expressed in VSMc of the fetal vasculature during late gestation (15). The expression of aT2r during fetal vasculogenesis influences the growth phenotype of VSMC via the modulation of the ERK cascade (28).…”
Section: Discussionmentioning
confidence: 99%
“…additionally, treatment with aT1r blockers (arBs) reduces the incidence of restenosis (12,13). aT2r is expressed abundantly in the fetal vasculature with rapid decline after birth, and is re-expressed in the adult vasculature under certain pathological cardiovascular conditions, such as vessel injury and inflammation (14,15). In injured vessels, aT1r is highly expressed, while aT2r is expressed at low levels (16).…”
mentioning
confidence: 99%